Effect of caffeine consumption on sleep quality of undergraduate medical students of Multan (Journal of Fatima Jinnah Medical University, 2023)
Background: Caffeine is extensively utilized as a stimulant of the central nervous system by more than 80% of the world’s population. About 94% of medical students are reported using caffeine which is likely to have a detrimental impact on sleep quality. The purpose of the study was to evaluate the relationship between caffeine consumption and sleep quality among non-obese. undergraduate medical studentsSubjects and methods: An Observational cross-sectional comparative study was carried out at Nishtar Medical University, Multan during the months of November and December 2022.Total 83, both male and female, non-obese undergraduate medical students (18-23 years old, BMI=18.5-24.9) selected by simple random sampling were included in this study, and they were divided into 3 groups on the basis of low (58 ± 29 mg/day), moderate (143±25 mg/day) or high (351±139 mg/day) caffeine consumption daily. Caffeine Consumption Questionnaire (CCQ) and Pittsburgh Sleep Quality Index Scale (PSQI) were used to assess the daily caffeine consumption (mg/day) and sleep quality, respectively. IBM SPSS-26 was used for data analysis. Mann-Whitney U test and Spearsman’s rho correlation were applied.Results: PSQI scores were high [11(8─16)] in highly caffeinated participants, moderate [7(5─9)] in moderately caffeinated participants, and low [3(1─6)] in low caffeinated [3(1─6)] participants (p=0.000). Low-caffeinated subjects had lower PSQI scores compared to moderately and highly caffeinated subjects (p=0.000 and p=0.000, respectively). PSQI scores in moderately caffeinated were also less as compared to highly caffeinated (p=0.000). Within the low caffeinated, moderately caffeinated, and highly caffeinated subjects caffeine consumption was positively correlated to PSQI scores (r=0.529, p=0.004), (r=0.579, p=0.002), (r=0.592, p=0.001) respectively.Conclusion: Increase in Caffeine consumption reduces sleep quality, implying that caffeine consumption and sleep quality are inversely related to each other.
Keywords: Caffeine consumption; Medical students; Quality of sleep